Hubungan Persepsi Matematika, Kemandirian Belajar dan Perhatian Orang Tua terhadap Prestasi Belajar Matematika - darmanto - darman; I Arcana; Dafid Setiana (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine whether there is a positive and significant correlation between perceptions of mathematics, independent learning, and parents' attention to mathematics learning achievement class X students of SMAN 1 Parittiga. The research method used is ex post facto. The population of this research is all students of class X at SMAN 1 Parittiga, with 35 students taken by cluster random sampling. The data was collected by questionnaire and test. The instrument used fulfills the validity and reliability test. Analysis prerequisite tests include normality, linearity, and multicollinearity. Hypothesis testing using multiple linear regression test and partial correlation test. The results showed that the tendency of high mathematics perception, very high independent learning, high parental attention and high mathematics learning achievement. The multiple correlation coefficient (R) is 0.867 with sig = 0.000 <0.05, and you get SE (X1) = 6.9%, SE (X2) = 61.2%, and SE (X3) = 7.2%.